Government's legal policy on the protection of women and children pre- and post-illegal marriages - Rahmatillah, Syarifah; Bustamam, Amrullah (Universitas Islam Negeri Ar-Raniry, 2023)
This study focuses on efforts made by the Aceh government to protect women and children before and after illegal marriages. The author uses a victimology theory approach to see the efforts made by the government in these cases. The author examines two problems; how the modus operandi of illegal marriage under state law occurs in Aceh and what countermeasures the Aceh Government has taken to protect women and children of Pre and Post-Illegal Marriage in Aceh. This research is a combination of Normative and Empirical research. The results indicate that the modus operandi of illegal marriage under state law occurs in Aceh includes siri marriage (unofficial, unregistered marriage) and its legal consequences, illegal polygamy by civil servants, early marriage, polyandrous marriage, Cina Buta marriage (muhallil or a proponent to reconcile a couple (wife and husband) who had divorced by triple divorce).The countermeasures implemented by the Aceh Government to protect women and children Pre and Post Illegal Marriage in Aceh include: conducting socialization to secondary schools about marriage following state law, issuing Aceh Governor Regulation no.25 of 2017 concerning the implementation of one-day service marriage validation (isbath nikah -marriage legalization- program during the conflict and tsunami), isbath nikah as a benchmark for data on the number of siri marriages, marriage dispensation for early marriage by teenagers, qanun policy on legalizing polygamy through qanun family law in Aceh illegal polygamy, and implementation of The Constitutional Court decisions on civil recognition of the status of children out of wedlock with biological fathers.